2020
DOI: 10.1101/2020.12.04.20241059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitive detection and quantification of SARS-CoV-2 in saliva

Abstract: Saliva has significant advantages as a test medium for detection of SARS-CoV-2 infection in patients, such as ease of collection, minimal requirement of supplies and trained personnel, and safety. Comprehensive validation in a large cohort of prospectively collected specimens with unknown SARS-CoV-2 status should be performed to evaluate the potential and limitations of saliva-based testing. We developed a saliva-based testing pipeline for detection of SARS-CoV-2 nucleic acids using real-time reverse transcrip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…No neutralization capabilities were detected for 2G12, PGT128, and PGT126 over a wide range of concentrations, while V H -FC ab8 demonstrated potent neutralization, in keeping with previous reports 23 . As antibody-dependent enhancement (ADE) of infection has been described for SARS-CoV-2 via engagement of cellular FcγRII receptors 25 , we evaluated the potential for antibody directed enhancement of infection (ADE) by these antibodies, in the FcγRII receptor expressing K562 erythroleukemic cell line 26 (Fig. 2 c).…”
Section: Resultsmentioning
confidence: 99%
“…No neutralization capabilities were detected for 2G12, PGT128, and PGT126 over a wide range of concentrations, while V H -FC ab8 demonstrated potent neutralization, in keeping with previous reports 23 . As antibody-dependent enhancement (ADE) of infection has been described for SARS-CoV-2 via engagement of cellular FcγRII receptors 25 , we evaluated the potential for antibody directed enhancement of infection (ADE) by these antibodies, in the FcγRII receptor expressing K562 erythroleukemic cell line 26 (Fig. 2 c).…”
Section: Resultsmentioning
confidence: 99%
“…Gallian et al used neutralizing antibody tests. However, there are studies indicating that not all individuals who recovered from a SARS-CoV-2 infection express detectable levels of neutralizing antibodies [ 21 ]. Zietz et al used swab tests, which were recently reported to differ substantially in analytical sensitivity and specificity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RNA-dependent RNA polymerase (RdRP) gene encodes an enzyme responsible for viral replication. These indispensable genes are the main target for the molecular detection of SARS-CoV-2 [12,[26][27][28][29]. Kakhki et al [30] PLOS ONE reported that ORF8 gene is a possible target for detecting COVID-19 and it is different from reported genes (RdRP, E and N genes), and ORF8 is fully specific to COVID-19 and has no cross-reactivity with other types of coronaviruses.…”
Section: Plos Onementioning
confidence: 99%